The semantic analysis of military lexical units in “Tamburlaine the great” written by Christopher Marlowe (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article military lexical units is analyzed based on the lexical-semantic use of the sentence “war” in Christopher Marlowe’s “Tamburlaine the Great”.